2017
DOI: 10.11646/phytotaxa.331.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A new species, two new combinations and notes on Fomitopsidaceae (Agaricomycetes, Polyporales)

Abstract: Rhodofomitopsis roseomagna sp. nov. is described as a new species from the Brazilian Atlantic forest based on morphological and molecular analyses. The species is characterized by the brownish to lilac, pileate basidiomata, round pores (5–6 per mm), and cylindrical to subcylindrical basidiospores (4–5 × 2.0–2.5 μm). Phylogenetic analyses based on combined ITS and nLSU rDNA sequences show that the new species belongs to the recently described genus Rhodofomitopsis. We also propose Rhodofomitopsis flabellata and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Soares, Ryvarden & Gibertoni were introduced as new species and F. bondartsevae (Spirin) A.M.S. Soares & Gibertoni was proposed as a new combination ( Soares et al 2017 ; Tibpromma et al 2017 ; Liu et al 2019 ). In the latest study, ten species have been recognised in the Fomitopsis pinicola complex ( Haight et al 2019 ; Liu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soares, Ryvarden & Gibertoni were introduced as new species and F. bondartsevae (Spirin) A.M.S. Soares & Gibertoni was proposed as a new combination ( Soares et al 2017 ; Tibpromma et al 2017 ; Liu et al 2019 ). In the latest study, ten species have been recognised in the Fomitopsis pinicola complex ( Haight et al 2019 ; Liu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, four species Fomitopsis caribensis B.K. Cui (Soares et al 2017;Tibpromma et al 2017;Liu et al 2019). In the latest study, ten species have been recognised in the Fomitopsis pinicola complex (Haight et al 2019;Liu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, phylogenetic analyses indicated that Fomitopsis is polyphyletic and the taxonomic position of Fomitopsis is still problematic ( Kim et al, 2005 , 2007 ; Justo and Hibbett, 2011 ; Ortiz-Santana et al, 2013 ). Recently, taxonomic and phylogenetic studies on Fomitopsis have been carried out and several new species have been described ( Li et al, 2013 ; Han et al, 2014 , 2016 ; Han and Cui, 2015 ; Soares et al, 2017 ; Haight et al, 2019 ; Liu et al, 2019 , 2021a ; Zhou et al, 2021 ). Han et al (2016) investigated phylogenetic relationships of Fomitopsis and its related genera and reported that species previously placed in Fomitopsis were divided into seven lineages: Fomitopsis s. s., Fragifomes B.K.…”
Section: Introductionmentioning
confidence: 99%